Arm Motor Recovery Using a Virtual Reality Intervention in Chronic Stroke: Randomized Control Trial. (January 2013) - Subramanian, Sandeep K.; Lourenço, Christiane B.; Chilingaryan, Gevorg; Sveistrup, Heidi; Levin, Mindy F.
Introduction . Despite interest in virtual environments (VEs) for poststroke arm motor rehabilitation, advantages over physical environment (PE) training have not been established. Objective . The authors compared kinematic and clinical outcomes of dose-matched upper-limb training between a 3D VE and a PE in chronic stroke. Methods : Participants (n = 32) were randomized to a 3D VE or PE for training. They pointed to 6 workspace targets (72 trials, 12 trials/target, randomized) for 12 sessions over 4 weeks with similar feedback on precision, movement speed, and trunk displacement. Primary (kinematics, clinical arm motor impairment) and secondary (activity level, arm use) outcomes were compared by time (PRE, POST, and follow-up, RET), training environment, and impairment severity (mild, moderate-to-severe) using mixed-model analyses of variance (ANOVAs). Results . Endpoint speed, overall performance on a reach-to-grasp task, and activity levels increased in both groups. Only participants in the VE group improved shoulder horizontal adduction at POST (9.5°) and flexion at both POST (6.3°) and RET (13°). Impairment level affected outcomes. After VE training, the mild group increased elbow extension (RET, 25.5°). The moderate-to-severe group in VE increased arm use at POST (0.5 points) and reaching ability at RET (2.2 points). The moderate-to-severe group training in PE increased reaching ability earlier (POST, 1.7 points) and both elbow extension (10.7°) and arm use (0.4 points) at RET, but these changes were accompanied by increased compensatory trunk displacement (RET, 30.2 mm). Conclusion . VE training led to more changes in the mild group and a motor recovery pattern in the moderate-to-severe group indicative of less compensation, possibly because of a better use of feedback.